1996
DOI: 10.21000/jasmr96010580
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Overland Flow Wetland Treatment Systems1 to Remove Nickel From Neutral Mine Drainage

Abstract: In 1992, two overland flow wetland treatment systems were built in existing natural wetlands in northeastern Minnesota to remove copper, nickel, cobalt and zinc from neutral mine drainage. Typical input metal concentrations ranged from 2-5 mg/L for nickel, to less than 0.1 mg/L for copper, cobalt and zinc. Flow rates were on the order of 75 L/min for both systems. The treatment systems covered 4200 m 2 and 7000 m' and contained a series of soil berms installed across the wetland, and about a 30 cm layer of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…If the treatment is to be sustainable and effective, not only must there be new metal removal capacity generated, but the metal must be retained within the wetland. Mass balances calculated on wetland test cells demonstrated that over 99% of the removed metals were associated with the 817 substrate and less than 1% of the total removal occurred in the vegetation (Eger et al, 1994). These results were consistent with earlier studies on metal removal in a white cedar wetland (Eger and Lapakko, 1988) and with data reported by others (Skousen et al, 1992, Wildeman et al, 1993.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…If the treatment is to be sustainable and effective, not only must there be new metal removal capacity generated, but the metal must be retained within the wetland. Mass balances calculated on wetland test cells demonstrated that over 99% of the removed metals were associated with the 817 substrate and less than 1% of the total removal occurred in the vegetation (Eger et al, 1994). These results were consistent with earlier studies on metal removal in a white cedar wetland (Eger and Lapakko, 1988) and with data reported by others (Skousen et al, 1992, Wildeman et al, 1993.…”
Section: Discussionsupporting
confidence: 90%
“…The ultimate goal of a passive treatment system is to provide permanent treatment. The major mode of metal removal in this system is assumed to be the same as observed in the initial test cell study (Eger et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations